Distributed point source model for wave propagation through multi-phase systems - Bhise, P.; Mukherjee, Abhijit; Sharma, S.; Ram, R. (2010)
Ultrasonic waves are used in identification of interfaces both in fluids and solids. It is imperative to numerically model these problems for their effective use. A newly developed technique, distributed point source method (DPSM), is gaining popularity in solution of these problems. The technique has been used to predict steady state conditions with a single frequency excitation. In this work, DPSM is extended to model transient waves propagation in multi-phase systems including multi-layered non-homogeneous fluid interfaces. Interface of two fluids is modeled using DPSM. Fast Fourier transformation (FFT) is used convert time domain signal into frequency domain and inverse FFT is used to transform the pressure and velocity signals back in time domain. Numerical results have been verified experimentally for transient wave propagation in homogenous and non-homogeneous fluids. © 2010 Springer Science+Business Media B.V.